Nanoscale surface chemistry directs the tunable assembly of silver octahedra into three two-dimensional plasmonic superlattices - Lee, Yih Hong (2018)
A major challenge in nanoparticle self-assembly is programming the large-area organization of a single type of anisotropic nanoparticle into distinct superlattices with tunable packing efficiencies. Here we utilize nanoscale surface chemistry to direct the self-assembly of silver octahedra into three distinct two-dimensional plasmonic superlattices at a liquid/liquid interface. Systematically tuning the surface wettability of silver octahedra leads to a continuous superlattice structural evolution, from close-packed to progressively open structures. Notably, silver octahedra standing on vertices arranged in a square lattice is observed using hydrophobic particles. Simulations reveal that this structural evolution arises from competing interfacial forces between the particles and both liquid phases. Structure-to-function characterizations reveal that the standing octahedra array generates plasmonic ‘hotstrips’, leading to nearly 10-fold more efficient surface-enhanced Raman scattering compared with the other more densely packed configurations. The ability to assemble these superlattices on the wafer scale over various platforms further widens their potential applications.